Why don't students like school? : a cognitive scientist answers questions about how the mind works and what it means for the classroom - Willingham, Daniel T. (San Francisco, CA : Jossey-Bass, 2009)
Cognitive scientist Dan Willingham has focused his acclaimed research on the biological and cognitive basis of learning and has a deep understanding of the daily challenges faced by classroom teachers. This book will help teachers improve their practice by explaining how they and their students think and learn revealing the importance of story, emotion, memory, context, and routine in building knowledge and creating lasting learning experiences. --from publisher description.
Includes bibliographical references (p. [214]-216) and index.
Keywords: Learning, Psychology of; Effective teaching